Factor substitution and demand for labour in the Northern Ireland engineering industry - Glass, J. C. (Statistical and Social Inquiry Society of Ireland, 1972)
The following analysis is not concerned with the question of what products should be produced in Northern Ireland, or what techniques of production should be used?rather it attempts to evaluate the existing policy of capital subsidisation in terms of its "potential" effect on the demand for labour in the Northern Ireland engineering industry. The purpose of the present study is co determine the effect, on employment, of the change in relative factor prices, (and where necessary to indicate the change in output required to offset this effect).
Read before the Society, 13 December 1971
Keywords: Factor substitution; Labour demand; Northern Ireland engineering industry; Factor intensities; 314.15